BIOLOGICAL STUDIES ON THE MEALYBUG, NIPAECOCCUS VIRIDIS (NEWSTEAD) ON VARIOUS HOST PLANTS - SAHA, A; GHOSH, AB. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The biology of the mealybug. Nipaecoccus viridis (Newstead) was studied in the laboratory on potted plants of Clerodendron infortunatum Goertn (Bhant), Artocarpus integra (Thumb) Merrill (Jackfruit), Citrus sp. (Citrus) and Glycine max Merrill (Soybean). The average developmental periods of male on bhant, jackfruit, citrus and soybean were 18.19, 16.89, 16.86 and 1623 days respectively, the corresponding periods of female being 16.19, 15.36, 15.46 and 14.62 days. The average preoviposition period, oviposition period and fecundity were 6.33 days, 9.67 days and 235 eggs on jackfruit, 7.33, 8.33 and 176.33 on citrus, 8.33, 7.66 and 78.67 on soybean and 7.67, 6.33 and 66.33 on bhant.